Mechanical properties of RF-sputtering MoS2 thin films. (12th June 2017) - Ramos, Manuel; Nogan, John; Ortíz-Díaz, Manuela; Enriquez-Carrejo, Jose L; Rodriguez-González, Claudia A; Mireles-Jr-Garcia, Jose; Ornelas, Carlos; Hurtado-Macias, Abel
Abstract: We present an evaluation of the hardness and Young's modulus properties of medium pressure sputtered molybdenum disulfide (MoS2 ) thin films by applying nano-indentation with continuous stiffness method combined with microstructure analysis using small angle x-ray diffraction, Raman, and an electron microscope in scanning and transmission mode. Our results indicate a vertical growth of MoS2 crystallites with stacking values of 7-laminates along the [0 0 1] direction and an average height of 105 nm, principal Raman vibrations at E 2 g 1 at 378 cm −1 and A1g at 407 cm −1 and an interplanar distance of 0.62 nm as confirmed by high-resolution transmission electron microscopy. An average hardness of H = 10.5 ± 0.1 GPa and elastic modulus of E = 136 ± 2 GPa from 0 to 90 nm of indenter penetration were found in these investigations.